Removal of granulosa theca cells tumor in the mare - . Amrozi; R. Harry Soehartono; Erly Rizka Adistya; Iga Mahardi; Hidayati Mukarromah; M. Ibnu Satria; Ho Kin Wai; Sugganya a/p Ravi (ARSHI Veterinary Letters, 2020)
Granulosa Theca Cells Tumor (GTCT) is the most common equine ovarian tumor that frequently occured in mare with indication of stallion like behaviour and nymphomania. A mare with stallion like behavior was diagnosed with ultrasound has GTCT with diameter of 147 mm of the left ovary and hypofunction of the right ovary. The GTCT was removed by midline laparotomy. Anesthesia was performed by using Xylazin and Ketamine and maintenance with Isoflurane. Large size of GTCT could be safely removed by abdominal midline surgery for extraction of tumor.